Direcionamento de feixes de baixa complexidade para redes sem fio multicast - Santos, Ricardo Brauner dos (2018)
In this work we study beamforming (BF) in a multicast system to maximize the minimum signal-to-interference-plus-noise ratio (SINR) among all user equipments (UEs). The strict definition of multicast is considered in this case, where the same information is transmitted to all users within a group. Multicasting is studied in two scenarios. In the first scenario we studied the impact of a relay with a single antenna in a BF system with a single-group multicast. In this context, two general approaches to solve the problem have been used. In the first approach the problem is divided into two sub-problems: the precoding problem, where a non-relayed solution of multicast BF is used to generate the transmission filter, and the repetition problem, where the solution of the precoding problem is adapted to improve the combined effective signal of the base station (BS) and the relay. In the second approach, two solutions are proposed that attempt to optimize the whole problem simultaneously. In the first one, the SDR algorithm is applied to the combined BS and relay channel. In the other solution, a heuristic algorithm called Relayed Iterative Rotation (RIR) iteratively optimizes the BF for the UE under the worst channel through a linear combination between the current pre-coding filter and the optimal filter for the worst UE. Simulation results have shown that the gain of the proposed scheme outweighs the loss of the additional transmission interval with gains in the minimum signal-to-noise ratio (SNR) and in the transmission rate of the system. We also studied the maximization of the minimum SINR in the BF scenario in a multicast system with multiple groups. The multigroup iterative rotation (MIRG) algorithm uses an approach similar to RIR, with additional iterations that reduce the interference of the other groups in the multicast group of the UE with the worst SINR. Simulation results showed that MIRG presents small losses in comparison to the algorithm based on SDR, but requiring a reduced computational complexity